Religion and the human sciences: an approach via spirituality - Helminiak, Daniel A. (State University of New York Press, 1998)
1Opening a Can of Worms1 --2Higher Viewpoints from Bernard Lonergan59 --3Revised Critical Correlation a la Don Browning161 --4The Perennial Philosophy of Ken Wilber213.